Effect of Equal Channel Angular Pressing (ECAP) on Wear Behavior of Al-7075 Alloy. (2015) - Chegini, M.; Fallahi, A.; Shaeri, M.H.
Abstract: Equal-channel angular pressing (ECAP) is an effective fabrication process for obtaining ultrafine grained materials. In order to investigate the effect of grain refinement during ECAP on wear properties of Al 7075 alloy, the specimens were pressed up to four passes by route BC at room temperature. Followed by ECAP, dry sliding wear tests have been conducted using a pin-on-disk machine under different loads of 10, 20 and 30N at a constant sliding speed of 0.23 ms -1 . Microstructural observations were undertaken using transmission electron microscopy (TEM) and the surface of worn specimens was investigated by scanning electron microscopy (SEM). The effect of load and ECAP process on the mass loss, have been explained with respect to microstructure and wear mechanism. Comparison of wear resistance of specimens shows that by using ECAP process, wear resistance of the specimens increases considerably due to the formation of very fine grains during ECAP.